Design of type-1 servo controller for grid voltage modulated direct-power control of single-phase grid-connected PV inverter - Eyad Radwan; Mutasim Nour; Ali Baniyounes; Khalid S. Al Olimat (Institute of Advanced Engineering and Science, 2021)
This paper presents direct control of active and reactive power using grid voltage modulation for single-phase grid-connected photovoltaic inverter. A design of type-1 servo system based on pole-placement method is proposed to control the power flow using a simplified multiple-input multiple-output (MIMO) model of the system. Phase-locked loop (PLL) with a quarter cycle time delay is used to estimate the grid phase angle for the purpose of performing the stationary and synchronous reference frame transformation. Unipolar pulse width modulation (PWM) technique is used to control a single-phase inverter with 2.7 KVA capacity connected to the photovoltaic system. The proposed controller can simply be tuned using minimum number of controller gains to achieve the transient and steady-state performance requirements. The proposed system, was capable of operating for a wide range of solar irradiance levels with a power factor in the range of 0.95 (leading/lagging), for the reactive power compensation purposes.